An introduction to English semantics and pragmatics - Griffiths, Patrick, 1942-2012 (Edinburgh textbooks on the English language., 2006)
An introduction to the linguistic study of meaning, this book outlines the meaning potential (semantics) of English and how language knowledge is put to use (pragmatics). As well as gaining a systematic overview of meaning in English, readers can learn how to argue for analyses. Among the significant concepts introduced are denotation, sense relations, event types, explicature, implicature, presupposition, metaphor, reference, speech acts and (at an elementary level) Generalised Quantifier Theory. Sense relations - such as antonymy and hyponymy - are presented as summarising patterns of entailment. The sense of a word is seen as the contributions it makes to the entailments carried by sentences. This textbook is compact and self-contained, offering: Discussion of many examples A theoretically informed approach Accessible organisation and style Detailed treatment of selected areas of English Consolidation and extension through exercises The chapters cover adjective, noun and verb meanings, situation types, figurative language, tense, aspect, modality, quantification, topic and focus. Explanations of entailment, compositionality and scope provide a foundation for subsequent study of formal semantics.